1999
DOI: 10.1002/(sici)1098-2264(199912)26:4<322::aid-gcc6>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐structure deletion mapping of 10q22–24 identifies regions of loss of heterozygosity and suggests that sporadic follicular thyroid adenomas and follicular thyroid carcinomas develop along distinct neoplastic pathways

Abstract: Previous studies have demonstrated frequent loss of heterozygosity (LOH) of markers on chromosome arm 10q in both follicular thyroid carcinomas (FTCs) and follicular thyroid adenomas (FAs). A novel tumor suppressor gene, PTEN, has been mapped to 10q23.3 and is the susceptibility gene for Cowden syndrome, an autosomal dominant disorder characterized by multiple hamartomas and a risk of benign and malignant tumors of the breast and thyroid. Studies examining the relationship of somatic PTEN status and follicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 27 publications
1
20
0
1
Order By: Relevance
“…However, results from several studies using primary prostate adenocarcinomas or low stage tumors detect few or no mutations in most tumors, indicating either that PTEN alteration is a late event in prostate cancer development or that another TSG critical in prostate cancer may lie close to PTEN (Dong et al, 1998;Feilotter et al, 1998;Orikasa et al, 1998). Similar ®ndings from studies with other types of cancers have been reported (Chiariello et al, 1998;Yeh et al, 1999;Yokomizo et al, 1998). The localization of the LAPSER1 to 10q24.3 near the PTEN locus and its likely involvement in cell growth or gene transcription modulation suggest that LAPSER1 may well represent the other TSG on this region.…”
Section: Discussionmentioning
confidence: 99%
“…However, results from several studies using primary prostate adenocarcinomas or low stage tumors detect few or no mutations in most tumors, indicating either that PTEN alteration is a late event in prostate cancer development or that another TSG critical in prostate cancer may lie close to PTEN (Dong et al, 1998;Feilotter et al, 1998;Orikasa et al, 1998). Similar ®ndings from studies with other types of cancers have been reported (Chiariello et al, 1998;Yeh et al, 1999;Yokomizo et al, 1998). The localization of the LAPSER1 to 10q24.3 near the PTEN locus and its likely involvement in cell growth or gene transcription modulation suggest that LAPSER1 may well represent the other TSG on this region.…”
Section: Discussionmentioning
confidence: 99%
“…Peaks are labeled with the peak height. Top panel, normal thyroid shows approximately equal peak heights; center panel, FTC from the same patient shows significant reduction in PPARg, lower panel, a tumor harboring the translocation shows significant upregulation of PPARg compared to GAPDH Since loss of heterozygosity on 3p has previously been reported in FTCs, LOH analysis was performed with the microsatellite markers D3S1259 and D3S3701, which flank PPARg, as previously described (Yeh et al, 1999). Three tumors showed LOH for both markers.…”
mentioning
confidence: 94%
“…The follicular-derived neoplasms (adenoma, carcinoma, and the follicular variant of papillary carcinoma) manifest overlapping cytomorphologic features and not infrequently pose diagnostic and treatment difficulties (1)(2)(3)(4). Previous molecular studies of thyroid tumors have been limited to individual or multiple targeted markers and have failed to define any diagnostic or prognostic markers (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Novel approaches are needed to identify reliable markers for pathological classification and to predict disease progression.…”
Section: Introductionmentioning
confidence: 99%